2019
DOI: 10.3390/medicina55110737
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Age Young Adults with Cerebral Palsy: Level of Participation and the Influencing Factors

Abstract: Background and Objectives: The aim of this study was to identify the level of participation in the context of the developmental transition from adolescence to adult life for young adults with cerebral palsy (CP) and the factors that had an influence on participation. Materials and Methods: Eighty-one young adults (16–21 years old) with CP and with normal or slightly decreased cognitive function participated in this study. Assessments were made using the Rotterdam Transition Profile (RTP) and the WHO Disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Service users were selected using a sampling frame that considered relevant characteristics identified in the literature, such as gender, 20 GMFCS level, 21,22 geographical location, and stage of transition. 21,22 We aimed to recruit 20 service providers encompassing health professionals and managers from child and adult services who provide care for young people with CP in Ireland. Health professionals were purposively sampled based on their profession, sector, cohort (paediatric or adult), and geographical region.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Service users were selected using a sampling frame that considered relevant characteristics identified in the literature, such as gender, 20 GMFCS level, 21,22 geographical location, and stage of transition. 21,22 We aimed to recruit 20 service providers encompassing health professionals and managers from child and adult services who provide care for young people with CP in Ireland. Health professionals were purposively sampled based on their profession, sector, cohort (paediatric or adult), and geographical region.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…Parents of young people with all severities of physical and intellectual disability were included. Service users were selected using a sampling frame that considered relevant characteristics identified in the literature, such as gender, 20 GMFCS level, 21,22 geographical location, and stage of transition. 21,22 We aimed to recruit 20 service providers encompassing health professionals and managers from child and adult services who provide care for young people with CP in Ireland.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…These observations have been documented in other countries, such as Norway where individuals with CP had lower odds of completing upper secondary education and had higher odds of receiving a disability pension ( 31 ). Similarly, a study from Latvia showed only 9% of adults having a paid job whereas 44% were still financially dependent as adults ( 32 ). This is consistent with several other studies reporting low employment rates in adults with CP ( 5 , 6 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 97%
“…“Late adulting” in several social and participation domains has been described in the Netherlands ( 20 ), and low levels of employment of people with CP have been reported in several countries ( 38 , 39 ). These difficulties have been found even in high functioning young adults with CP who have no intellectual disability ( 40 ) and in other dimensions of participation like “having a cohabiting partner” or “having a biological descendance” ( 41 ). This parallel evolution between systems throughout the wide transition period from childhood to adulthood requires policy makers to develop national strategies that are adapted to the changing needs of individuals with CP in all domains.…”
Section: Discussionmentioning
confidence: 99%